O-25 MUNIX alteration in three consecutive muscles innervated by ulnar nerve in Amiyotrophic Lateral Sclerosis. Issue 7 (July 2019) - Gunes, Taskin; Sirin, Gorkem; Isak, Baris
Abstract : Background: The motor unit number index (MUNIX) method is used to estimate alterations attributed to changes in number and size (MUSIX) of motor units (MUs) using the compound muscle action potential (CMAP) and surface electromyographic interference pattern (SIP). Material and methods: In sixteen patients with Amyotrophic Lateral Sclerosis (ALS) and 16 controls, compound muscle action potentials (CMAP), MUNIXs and MUSIXs were recorded from flexor carpi ulnaris (FCU), abductor digiti minimi (ADM), and first dorsal interosseous (FDI) muscles. Results: In ALS patients, mean values of MUNIXs recorded form FCU (76.7 ± 24.01 vs 71.5 ± 32.4, P = 0.22), ADM (130.3 ± 1.4 vs. 66.4 ± 2.3, P = 0.008), and FDI (181.8 ± 1.3 vs. 63.6 ± 2.8, P = 0001) muscles were lower and MUSIXs of FCU (59.9 ± 11.6 vs. 54.4 ± 13.4, P = 0.6), ADM (85.6 ± 1.4 vs. 99.1 ± 1.6, P = 0.34), and FDI (72.9 ± 1.2 vs. 99.9 ± 1.6, P = 0.03) were higher than controls. CMAPs deteriorated in proximal (i.e., FCU; 6 ALS vs. 0 controls, P = 0.009) muscle more than distal (i.e., ADM; 5 ALS vs. 0 control, P = 0.02 and FDI; 3 ALS vs. 1 control, P = 0.3) while MUNIXs deteriorated in distal (i.e., FDI; 9 ALS vs. 0 control, P = 0.003) more than proximal (i.e., ADM; 7 ALS vs. 1 control, P = 0.02, and FCU; 1 ALS vs. 0 control, P = 0.5) muscles. Conclusions: Unlike CMAPs, MUNIX was considered to define denervation process overwhelming the impact of re-innervation using SIPs. In addition to utility in long term assessment of ALS patients, MUNIX could be used to estimate quantitative alterations in motor units for diagnostic purpose.